2019
DOI: 10.1002/nop2.290
|View full text |Cite
|
Sign up to set email alerts
|

Struggling to be seen and understood as a person – Chronic back pain patients’ experiences of encounters in health care: An interview study

Abstract: Aim The aim of this study was to describe how patients with chronic back pain experience encounters with health care. Persons with chronic back pain are a stigmatized group often treated based on stereotypes, which may lead to misunderstandings and create frustrated patients and healthcare personnel. Few studies have examined the generic aspects of quality of care in this context. Design A descriptive design with a qualitative approach was used. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…The finding that informants experienced the rejection as an extra burden to their struggles resonates with previous studies' findings on experiences of distrust, disbelief and pain invalidation in chronic pain patients' consultations within the health care system [34,35]. These experiences have been linked to powerlessness and mistrust [29], to which the informants reports in the current study of resignation, frustration, sadness and anger can be added.…”
Section: Desiring a Chance To Be Heard And Seensupporting
confidence: 88%
See 1 more Smart Citation
“…The finding that informants experienced the rejection as an extra burden to their struggles resonates with previous studies' findings on experiences of distrust, disbelief and pain invalidation in chronic pain patients' consultations within the health care system [34,35]. These experiences have been linked to powerlessness and mistrust [29], to which the informants reports in the current study of resignation, frustration, sadness and anger can be added.…”
Section: Desiring a Chance To Be Heard And Seensupporting
confidence: 88%
“…This finding adds to previous reports of that persons with chronic pain have difficulties accessing health care [10,11,27] and to the literature on experienced injustice among chronic pain patients [28]. For instance, studies have found that this group of patients have experienced refused access to treatments because healthcare providers assumed they would not benefit from them [29], and that persons with neuropathic pain found interacting with the healthcare system as a struggle [17].…”
Section: A Total Rejectionsupporting
confidence: 67%
“…Management of LBP has remained a challenge, and clinical decision-making for referrals to PT, pain management, and other specialists is currently inconsistent [ 13 , 14 ]. Additionally, patients with LBP have expressed concerns that care is not individualized [ 36 ]. Our study demonstrated differences in the utilization patterns of patients across the symptom classes.…”
Section: Discussionmentioning
confidence: 99%
“…People with LBP manage and negotiate aspects of their pain with healthcare professionals, significant others and social systems (Holloway et al, 2000). Unfortunately, they are sometimes treated impersonally by healthcare professionals (Hadi et al, 2017), who have to follow guidelines and routines and miss listening to individual’s wishes and preferences (Allvin et al, 2019). In a study by Allvin et al (2019), for example, participants with chronic back pain tried to explain their feelings and preferences to their clinicians, but felt obligated to comply and adapt to care requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, they are sometimes treated impersonally by healthcare professionals (Hadi et al, 2017), who have to follow guidelines and routines and miss listening to individual’s wishes and preferences (Allvin et al, 2019). In a study by Allvin et al (2019), for example, participants with chronic back pain tried to explain their feelings and preferences to their clinicians, but felt obligated to comply and adapt to care requirements. This obligation often made them feel vulnerable, frustrated and not seen nor understood as a person.…”
Section: Discussionmentioning
confidence: 99%